Development of Exploration Criteria for Massive Sulfides on Slow-Spreading Ridges – Lessons Learned from the TAG Hydrothermal Field - Sebastian Graber; Sven Petersen; Meike Klischies; Florent Szitkar; Isobel Yeo (International Marine Minerals Society, 2018)
Technological advances and the shift towards green energies in the last decades have led to a substantial increase in the demand for metal resources. With rising political tension, and quasi-monopolistic production of some key metals, a secured supply chain cannot be guaranteed [1]. Therefore, the focus of the international research community and mining companies has expanded to the seafloor, looking for additional resources. The seafloor may have the potential to contribute significantly to a secure metal supply in the future. However, we have only investigated a fraction of our oceans in sufficient detail to assess the global resource potential. A detailed exploration of the vast seafloor is currently economically not feasible, due to its extremely time-consuming and costly nature. Seafloor massive sulfides generally form along the active plate boundaries and at active volcanoes in arc settings. However, the resources are not evenly distributed on the seafloor. Large deposits tend to be more common along slow-spreading and ultra-slow- spreading ridges that make up the majority of the global mid-ocean ridge system [2]. Therefore, it is important to establish geological models and exploration criteria in order to narrow down the permissive areas, which are likely to accommodate economically interesting deposits. Based on a detailed study of the TAG hydrothermal field in the central Atlantic Ocean, hosting a large active mound as well as several inactive mounds, we develop exploration methods and criteria to define areas of potential massive sulfide occurrences along slow-spreading sections.